A systematic review of inclusive pedagogical research using the CIRTL inclusive pedagogy framework: multi-disciplinary and STEM perspectives, current trends and a research agenda - Angela G. Jackson-Summers; Karina L. Mrakovcich; Joshua P. Gray; Corinna M. Fleischmann; Tooran Emami; Eric J. Page (Springer, 2024)
Abstract In higher education, student retention challenges and advancing student diversity are not new. Such institutional student retention challenges and student diversity promotions continue to require more focus and effort. A means to help address student retention and improve student diversity through faculty engagement in classrooms is inclusive pedagogy. In this study, we inform researchers and practitioners about the current state of inclusive pedagogical research, including gaps addressing further needs of inclusive pedagogical research from a multi-disciplinary perspective, including science, technology, engineering, education, math, humanities, management, and economics. We also share a non_STEM-Focused versus STEM-Focused inclusive pedagogy literature perspective. Using the Center for the Integration of Research, Teaching and Learning (CIRTL) framework, we reviewed 304 articles to help shed light on existing inclusive pedagogy, focusing on three core competencies: inclusive communications, inclusive pedagogy practices, and the design of inclusive curriculum. Based on our discussion of findings and related implications for future research, we conclude that inclusive pedagogical research warrants improvement across all core competencies and academic disciplines to strengthen improvement of this research field. This study contributes to researchers and practitioners, especially those focusing inclusive pedagogy in classrooms, as well as the body of inclusive pedagogy knowledge.